Access control model based on trusted computing for integrated avionics system - CUI Xi-ning1; 2; SHEN Yu-long1; MA Jian-feng1 (Tongxin xuebao)
Integrated avionics system is a highly integrated and modularized system.It strongly requires the reliability of platform, the confidentiality and integrity of information.Software alone does not provide an adequate foundation for building a high-assurance trusted platform.The access control policies based on trusted hardware and trusted computing technologies were focused.By using BLP model and BIBA model, an access control model was brought for ensuring the confidentiality and integrity of information, which greatly improved integrated avionics system’s security.